Description and grammatical analysis of Persian to Persian teaching series of Jameâat al-Mostafa al-âalamiye books - Nafise Raisi; Mohsen Mohammadifesharaki (Literary Arts, 2016)
Â AbstractÂ Persian as the second language of the world of Islam is closely related to the teachings of this divine religion, so learning Persian besides Islamic and Shia teachings would be helpful for Islamic scholars. In this regard, Jameâat al-Mostafa al-âalamiye in the context of the Persian language tries to train Islamic scholars, translators and missioners.Â Center of language education and Islamic teachings which is the subset of Jameâat al-Mostafa, has formulated a collection of eight books named Persian to Persian teaching which is taught in different centers of Jameâat al-Mostafa inside and outside of the country.Â High goals of this Shia association represents the importance of authoring and analyzing education books. So their accuracy needs more attention and research. This essay aimed at describing and grammatical analyzing of this educational series. The present study deals with the importance and methods of teaching grammar to non-Persian speakers after introducing the Jameâat al-Mostafa al-âalamiye; also, besides introducing the required grammatical issues, it describes eight volumes books of teaching Persian-to-Persian grammatically.Â Then the grammatical difficulties of these books are investigated in ten separate sections with giving some examples. The study ends with providing some strategies to improve the grammatical issues of this educational set and other books of teaching Persian language to non-Persian speakers.Â In the early years after the Islamic revolution, some foreign students came to Iran to study Islamic studies so the supervisory board of non-Iranian students was established to answer and to organize their educational and livelihood status in 1979. âJameâat al-Mostafa al-âalamiyeâ was founded in Qom and other cities after the continuous changes in 2007. This center tries to grow the Islamic scholar, translator, and missionary by teaching Persian language; in this way, center of language and Islamic studies considered as a subset of Jameâat al-Mostafa has published a set of teaching Persian- to- Persian in eight books that are teaching in different centers of Jameâat al-Mostafa in country and abroad now. The valuable goals of this Shiite institution in spreading Islam show the importance and sensitivity of writing and analyzing its educational books so it is clear that their rightness and accuracy need more attention and study. The purpose of this study is to describe and to do grammatical criticism on this educational set. In this study, after expressing the importance of grammar in teaching Persian language to non-Persian speakers, the methods of writing grammar in Persian language and the required grammatical issues for the students whose native language is not Persian will be dealt. Teaching Persian language in Persian-to-Persian books is directly done without using the intermediate language or translation. These books have an instructional, traditional, and inductive approach, grammatically. In this set, grammatical rules are presented in a part of book namely "points". Examples of each section are presented in the form of sentence not text and they are usually ended with the related exercises. However, before dealing with the grammatical problems of this set, linguistic concepts and grammatical rules of every book are described in separate tables. In this study, the grammatical problems of teaching Persian-to Persian books are presented in ten separate sections and some examples are suggested for each one includingÂ  1. Grammatical incorrectness Â 2. Incomplete definition of grammatical rules and points Â 3. Grammatical incompleteness Â 4. Repetition of materials Â 5. Ignoring the logical order and sequence of grammatical topics Â 6. The presence of confusion in naming grammatical terms Â 7. Grammatical patterns Â 8. The presence of confusion in grammatical footnotes Â 9. The writing and editing difficulties in expressing grammatical issues Â 10. Incomplete pictures Â By considering this study, the following items are recommended to improve the grammatical structure of teaching Persian-to-Persian: Â The review of design and curriculum of grammar and its compatibility with the updated materials by using the specialists' board of Persian grammar, teaching Persian language and its grammar based on the students' needs of learning these books to use Persian texts, cultures, to get four language skills, compatibility of grammatical concepts, and to adopt the same approach in designing and improving them, dependence on learning grammatical issues based on simply grammatical, scientific, and single-legal patterns, presenting efficiently grammatical issues to increase the students' four skills, using context especially communicational and conversational texts useful for students in teaching Persian grammar to understand the value of grammatical structures and their role, the sequence of materials and grammatical structures based on their frequency in language, ignoring the exceptional and rare items in grammatical issues, considering and emphasizing on teaching method from easy up to hard to make motivation and self-confidence in students and preparing them for next teachings, to cause the study of the regular grammar being delayed to advanced stages.